Application of optimal design methodologies in retrofitting natural gas combined cycle power plants with CO2 capture. (1st January 2016) - Pan, Ming; Aziz, Farah; Li, Baohong; Perry, Simon; Zhang, Nan; Bulatov, Igor; Smith, Robin
Highlights: A new approach is proposed for retrofitting NGCC power plants with CO2 capture. HTI techniques are developed for improving heat recovery in NGCC power plants. EGR techniques are developed to increase the process overall energy efficiency. The proposed methods are efficient for practical application. Abstract: Around 21% of the world's power production is based on natural gas. Energy production is considered to be the significant sources of carbon dioxide (CO2 ) emissions. This has a significant effect on the global warming. Improving power plant efficiency and adding a CO2 capture unit into power plants, have been suggested to be a promising countermeasure against global warming. This paper presents a new insight to the application of energy efficient technologies in retrofitting natural gas combined cycle (NGCC) power plants with CO2 capture. High fidelity models of a 420 MW NGCC power plant and a CO2 capture plant with CO2 compression train have been built and integrated for 90% capture level. These models have been then validated by comparisons with practical operating data and literature results. The novelty of the paper is to propose optimal retrofitting strategies to minimize the efficiency penalty caused by integrating carbon capture units into the power plant, including (1) implementing heat transfer intensification techniques to increase energy saving in the heat recovery steam generator (HRSG) of the power plant; (2) extracting suitable steam from the HRSG to supply the heat required by the capture process, thus on external heat is purchased; (3) employing exhaust gas recirculation (EGR) to increase the overall energy efficiency of the integrated process, which can benefit both power plant (e.g. increasing power plant efficiency) and capture process (e.g. reducing heat demands). Compared with the base case without using any integrating and retrofitting strategies, the optimal solution based on the proposed approaches can provide sufficient heat to CO2 capture process, and keep the same power generation. The optimal solution shows that, the flue gas flow-rate is reduced 33% in the inlet of CO2 capture process, heat demand in CO2 capture decreases 4.3%, heat output from the power plant increases from 0 MW to 133 MW, and more than 22% of profit is obtained in the integrated system. This demonstrates the validity and efficiency of the proposed approaches in retrofitting existing NGCC power plants with CO2 capture.